Trafficking of a multifunctional protein by endosomal microautophagy: linking two independent unconventional secretory pathways. Issue 4 (14th January 2019) - Chauhan, Anoop Singh; Kumar, Manoj; Chaudhary, Surbhi; Dhiman, Asmita; Patidar, Anil; Jakhar, Priyanka; Jaswal, Pallavi; Sharma, Kapil; Sheokand, Navdeep; Malhotra, Himanshu; Raje, Chaaya Iyengar; Raje, Manoj
ABSTRACT: During physiologic stresses, like micronutrient starvation, infection, and cancer, the cytosolic moonlighting protein glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) is trafficked to the plasma membrane (PM) and extracellular milieu (ECM). Our work demonstrates that GAPDH mobilized to the PM, and the ECM does not utilize the classic endoplasmic reticulum–Golgi route of secretion; instead, it is first selectively translocated into early and late endosomes from the cytosol via microautophagy. GAPDH recruited to this common entry point is subsequently delivered into multivesicular bodies, leading to its membrane trafficking through secretion via exosomes and secretory lysosomes. We present evidence that both pathways of GAPDH membrane trafficking are up‐regulated upon iron starvation, potentially by mobilization of intracellular calcium. These pathways also play a role in clearance of misfolded intracellular polypeptide aggregates. Our findings suggest that cells build in redundancy for vital cellular pathways to maintain micronutrient homeostasis and prevent buildup of toxic intracellular misfolded protein refuse.—Chauhan, A. S., Kumar, M., Chaudhary, S., Dhiman, A., Patidar, A., Jakhar, P., Jaswal, P., Sharma, K., Sheokand, N., Malhotra, H., Raje, C. I., Raje. M. Trafficking of a multifunctional protein by endosomal microautophagy: linking two independent unconventional secretory pathways. FASEB J. 33, 5626–5640 (2019). www.fasebj.org